Analysis of Content, Meaning, and Cultural Values in Balinese Lontar Manuscripts: A Case Study of Gending Gambang at Gambang Kwanji Sempidi - Gek Diah Desi Sentana; I Nyoman Mariyana (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study examines the content, meaning, and cultural values embedded in a specific corpus of Balinese lontar manuscripts used in the Gending Gambang tradition at Gambang Kwanji Sempidi, Bali. Unlike previous studies that treat lontar manuscripts in a general or catalog-based perspective, this research focuses on an intrinsic case study of a living manuscript tradition that is actively integrated into musical and ritual practice. The main research gap addressed in this study lies in the limited interpretive analysis of lontar manuscripts as contextual cultural texts, particularly in relation to their role in sustaining embodied artistic knowledge in contemporary Balinese society. This research employs a qualitative intrinsic case study design supported by hermeneutic, semiotic, and philological perspectives. Hermeneutics is used to interpret meaning within cultural and historical contexts, semiotics is applied to analyze symbolic structures in the manuscript notation system, while philology supports textual reading and interpretation of the lontar content. Data were collected through interviews, participant observation, documentation, and textual analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the lontar manuscripts of Gending Gambang function not only as textual artifacts but also as epistemic instruments that transmit musical knowledge, cultural memory, and ritual authority. The meanings embedded in the manuscripts are constructed through symbolic notation systems that require interpretive reading within communal practice. Furthermore, the cultural values identified include religiosity, artistic discipline, social cohesion, and intergenerational knowledge transmission. The novelty of this study lies in its integration of hermeneutic-semiotic interpretation with philological reading within a single intrinsic ethnocultural case study, demonstrating that lontar manuscripts operate as living cultural texts rather than static literary relics. The study contributes to the development of classical literature studies by positioning lontar manuscripts within contextual cultural literacy, ethnopedagogical practice, and community-based heritage preservation. This reinforces the relevance of lontar manuscripts as dynamic knowledge systems that continue to function within contemporary cultural ecosystems.